Aberrant gene expression profiles in Mediterranean sea urchin reproductive tissues after metal exposures. (February 2019) - Di Natale, Marilena; Bennici, Carmelo; Biondo, Girolama; Masullo, Tiziana; Monastero, Calogera; Tagliavia, Marcello; Torri, Marco; Costa, Salvatore; Ragusa, Maria Antonietta; Cuttitta, Angela; Nicosia, Aldo
Abstract: Marine organisms are simultaneously exposed to numerous pollutants, among which metals probably represent the most abundant in marine environments. In order to evaluate the effects of metal exposure at molecular level in reproductive tissues, we profiled the sea urchin transcriptional response after non-lethal exposures using pathway-focused mRNA expression analyses. Herein, we show that exposures to relatively high concentrations of both essential and toxic metals hugely affected the gonadic expression of several genes involved in stress-response, detoxification, transcriptional and post-transcriptional regulation, without significant changes in gonadosomatic indices. Even though treatments did not result in reproductive tissues visible alterations, metal exposures negatively affected the main mechanisms of stress-response, detoxification and survival of adult P. lividus. Additionally, transcriptional changes observed in P. lividus gonads may cause altered gametogenesis and maintenance of heritable aberrant epigenetic effects. This study leads to the conclusion that exposures to metals, as usually occurs in polluted coastal areas, may affect sea urchin gametogenesis, thus supporting the hypothesis that parental exposure to environmental stressors affects the phenotype of the offspring. Highlights: Non-lethal metal exposures do not modify sea urchin gonadosomatic indices. Metal exposures affect mRNA expression profile in sea urchin reproductive tissues. Coexposures attenuates transcriptional response.